Single and Multi-Objective Optimization of Permanent Magnet Synchronous Motor - Cvetkovski, Goga; Petkovska, Lidija (IEEE, 2022)
The optimal design of electrical machines or optimization of certain machine parameters has occupied the researchers and the academia for a long period of time. In this work a single objective and a multi-objective optimization approach is realized and presented. Genetic algorithm is used as an optimization tool. The efficiency of the motor, the cogging torque and the total weight of the active materials are applied as an objective function in the single objective optimization. The combination of those three functions is applied in the multi-objective optimization. Comparative results from all the optimization procedures are presented.